KLASIFIKASI DATA LULUSAN SMPN 3 TULAKAN MENGGUNAKAN METODE NAÏVE BAYES - Lesta Lia Regitaningtyas; Tamara Maharani Maharani; Bagus Hikmawan Hikmawan (Lambung Mangkurat University, 2022)
Alumni of junior high school students have a fairly diverse distribution of data. With a case study at SMP Negeri 3 Tulakan, the basis for this research is to predict the distribution of junior high school graduates in the following year. The data mining process is assisted by the WEKA application. The classification used is the nave Bayes classification using the test training set mode and cross validation folds 10. The results of this study from the test training set mode got Correctly Classified 83.2787% and Incorrectly Classified 16,7213% while in cross validation it got Correctly Classified 81.3115% and Incorrectly Classified 18.6885%. The percentage of accuracy value shows the effectiveness of the Admissions dataset applied to the Naïve Bayes Classification method which reaches 80%. The results of this study indicate that the data classification using Naïve Bayes has an accuracy level that is close to accurate.Keywords: data mining, Naive Bayes classification, student data, WEKA applicationAlumni siswa SMP memiliki persebaran data yang cukup beragam. Dengan studi kasus di SMP Negeri 3 Tulakan, menjadikan landasan pada penelitian ini untuk memprediksi persebaran lulusan Sekolah Menengah Pertama pada tahun selanjutnya. Proses data mining dibantu oleh aplikasi WEKA. Adapun klasifikasi yang digunakan adalah klasifikasi naïve bayes dengan menggunakan mode test training set dan cross validation folds 10. Hasil dari penelitian ini dari mode test training set mendapat sebesar Correctly Classified 83.2787% dan Incorrectly Classified 16.7213% sedangkan pada cross validation mendapat sebesar Correctly Classified 81.3115% dan Incorrectly Classified 18.6885%. Nilai persentase akurasi menunjukkan efektifitas dataset Admissions yang di terpkan pada metode Naive Bayes Classification yang mencapai 80%. Dari hasil penelitian ini menunjukkan bahwa klasifikasi data menggunakan Naive Bayes memiliki tingkat akurasi yang mendekati akurat.Kata kunci: data mining, klasifikasi naïve bayes, data siswa, aplikasi WEKA.